2021
DOI: 10.1111/cas.14805
|View full text |Cite
|
Sign up to set email alerts
|

KHDRBS3 promotes multi‐drug resistance and anchorage‐independent growth in colorectal cancer

Abstract: 5‐Fluorouracil (5‐FU) is one of the most frequently used pharmacological agents in the treatment of colorectal cancer (CRC). Resistance to chemotherapy is a major cause of treatment failure of CRC, and it is a well known fact that cancer stem cells play a significant role in the acquisition of drug resistance. In this study, we focused on the KHDRBS3 gene that encodes KH RNA Binding Domain Containing, Signal Transduction Associated 3. We first clarified the relationship between KHDRBS3 and 5‐FU resistance. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Numerous studies have shown that adjuvant 5-FU-based chemotherapy can improve the 5-year overall survival (OS) of stage II and III patients compared to surgery alone ( 41 , 42 ). However, the prognosis of such patients still remains poor, mainly due to 5-FU resistance ( 43 , 44 ). Herein, we have made several novel observations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that adjuvant 5-FU-based chemotherapy can improve the 5-year overall survival (OS) of stage II and III patients compared to surgery alone ( 41 , 42 ). However, the prognosis of such patients still remains poor, mainly due to 5-FU resistance ( 43 , 44 ). Herein, we have made several novel observations.…”
Section: Discussionmentioning
confidence: 99%
“… Abbreviated name Full official name Classification Intervention mechanism References 1 ACBP Anticancer bioactive peptide Novel bioactive peptide ACBP can inhibit phospho-LRP6 and stimulate phospho-β-catenin. [ 168 ] 2 ND MiR-377-3p MicroRNA Directly target ZEB2 and XIAP to inhibit Wnt/β-catenin signaling [ 169 ] 3 DHME Dehydroxyhispolon methyl ether Hispolon derivatives Inhibits β-catenin-mediated T cell factor (TCF)-dependent transcriptional activity [ 170 ] 4 ND SSTC3 New small molecule CK1α activator The target CK1α inhibits the growth of mouse CRC xenografts and attenuates the growth of patient-derived metastatic CRC xenografts [ 171 ] 5 CQD Chlorquinaldol Bacteriostatic agent Inhibit the acetylation of β-catenin, destroy the interaction between β-catenin and T cell factor 4 (TCF4), and reduce the binding of β-catenin to Wnt target gene promoters, and down-regulate the expression of these target genes [ 172 ] 6 ND KY7749 Compound Inhibit the proliferation and transformation of CRC cells, independently of β-catenin degradation of Ras [ 173 ] 7 ND Niclosamide Antihelminth compound Inhibit Wnt/β-catenin pathway activation, down-regulate Dvl2, and reduce downstream β-catenin signal transduction [ 174 ] 8 ND KHDRBS3 Genes encoding KH RNA binding domains, signal transduction related 3 KHDRBS3 may play a key role in acquiring stem cell characteristics (such as drug resistance and spheroid/organoid formation) by regulating the expression of CD44 variants and the Wnt signaling pathway [ 175 ] 9 ND KYA1797K ...…”
Section: Drugs and Inhibitorsmentioning
confidence: 99%
“…A crucial NF-κB regulator, Sam68 (KHDRBS3), was also observed to be elevated in LPS-treated tumor enteroids, along with the genes GEN1 , KRIT1 , CENPF , and STYK1 . Sam68 (KHDRBS3) exhibited a prognostic significance in various malignancies and was elevated in cancer cell lines [ 79 , 80 , 81 ]. Sam68 (KHDRBS1), a homolog of KHDRBS3, was found to be co-expressed with cancer-related genes in the genome-wide analysis [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while LPS treatment increased the proliferation and expression of the GEN1 , KRIT1 , CENPF , CPLANE1 , STYK1 , and KHDRBS3 genes, it decreased the expression of the cancer associated LOC610994 , Gpatch4 , SLC7A1 , ATP13A2 , and TEX45 genes [ 75 , 81 , 82 , 83 , 87 ] in tumor enteroids. This could imply that LPS has some anticancer activity.…”
Section: Discussionmentioning
confidence: 99%